Bimbingan Konseling dalam Menangani Penderita Skizofrenia Melalui Pendekatan Nilai dan Spiritual - Uzlifah, Tamimatu (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2019)
The purpose of this study is to find out how to deal with schizophrenia patients using a spiritual approach. Data collection was carried out by observation, interviews and documentation at the Rehabilitation Home for Pondok Tetirah Dzikir Kuton Tegaltirto Berbah Sleman Yogyakarta. In fostering schizophrenia patients, the Institution for Rehabilitation uses a therapeutic service program which is also an integrated service program, spiritually carried out by religious methods namely Tareqat Qadariyah al-Naqsyabandiyah (TQN) Suryalaya which is therapeutic: bathing repentance, prayer, dzikr, khataman, manaqiban, fasting, pilgrimage, religious studies and other practices. Then physically, it is carried out with routine medical examinations, exercise, and community service. All of that is done to train the physical and spiritual health of a patient with schizophrenia. From the results of the study, it can be seen that this approach is able to handle schizophrenia patients through planting values and spirituality into their souls, although it cannot be said to be fully healed, but this development can minimize the occurrence of undesirable things and when the soul is sick the treatment starts with his soul also.